Novel phthalimides regulating PD-1/PD-L1 interaction as potential immunotherapy agents - Chengliang Sun; Yao Cheng; Xiaojia Liu; Gefei Wang; Wenjian Min; Xiao Wang; Kai Yuan; Yi Hou; Jiaxing Li; Haolin Zhang; Haojie Dong; Liping Wang; et al. (Elsevier, 2022)
Programmed cell death 1(PD-1)/programmed cell death ligand 1(PD-L1) have emerged as one of the most promising immune checkpoint targets for cancer immunotherapy. Despite the inherent advantages of small-molecule inhibitors over antibodies, the discovery of small-molecule inhibitors has fallen behind that of antibody drugs. Based on docking studies between small molecule inhibitor and PD-L1 protein, changing the chemical linker of inhibitor from a flexible chain to an aromatic ring may improve its binding capacity to PD-L1 protein, which was not reported before. A series of novel phthalimide derivatives from structure-based rational design was synthesized. P39 was identified as the best inhibitor with promising activity, which not only inhibited PD-1/PD-L1 interaction (IC50 = 8.9 nmol/L), but also enhanced killing efficacy of immune cells on cancer cells. Co-crystal data demonstrated that P39 induced the dimerization of PD-L1 proteins, thereby blocking the binding of PD-1/PD-L1. Moreover, P39 exhibited a favorable safety profile with a LD50 > 5000 mg/kg and showed significant in vivo antitumor activity through promoting CD8+ T cell activation. All these data suggest that P39 acts as a promising small chemical inhibitor against the PD-1/PD-L1 axis and has the potential to improve the immunotherapy efficacy of T-cells.